Detecting preservation and reintroduction sitesfor endangered plant species using a two-step modelingand field approach - Rusconi, Olivia; Broennimann, Olivier; Storrer, Yannick; Le Bayon, Renée-Claire; Guisan, Antoine; Rasmann, Sergio (My University, 2022)
To withstand the surge of species loss worldwide, (re)introduction of endan-gered plant species has become an increasingly common technique in conser-vation biology. Successful (re)introduction plans, however, require identifyingsites that provide the optimal ecological conditions for the target species tothrive. In this study, we propose a two-step approach to identify appropriate(re)introduction sites. The first step involves modeling the niche and distribu-tion of the species with bioclimatic and topographical predictors, both at conti-nental and at national scales. The second step consists of refining thesebioclimatic predictions by analyzing stationary ecological parameters, such assoil conditions, and relating them to population-level fitness values. We dem-onstrate this methodology using Swiss populations of the lady's slipper orchid(Cypripedium calceolusL., Orchidaceae), for which conservation plans haveexisted for years but have generally been unfruitful. Our workflow identifiedsites for future (re)introductions based on the species requirements for mid-to-sunny light conditions and specific soil physico-chemical properties, such asbasic to neutral pH and low soil organic matter content. Our findings showthat by combining wide-scale bioclimatic modeling with fine scale field mea-surements it is possible to carefully identify the ecological requirements of atarget species for successful (re)introductions.
Keywords: ecological niche; endangered plants; ensemble forecasting; population fitness; red list; restoration; soil properties